MEMBANGUN KEBIJAKAN PUBLIK UNGGUL DI ERA DEMOKRASI - Riant Nugroho (Universitas Jenderal Ahmad Yani, 2018)
The superiority of a nation is increasingly determined by the Government's ability of the nation to produce superior policies. The era of Indonesian democracy since the 1998 Reformation has not yet promised a public policy blow. The question is how to build capacity to build superior public policy. The answer is offered in the form of Ten Principles (also called